MARJINALISASI MASYARAKAT PEDESAAN Studi di Desa Cipacing, Kecamatan Jatinangor, Kabupaten Sumedang - Muhammad Fedryansyah (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2019)
This research focuses on marginal communities in the countryside. Marginal communities who are poor, among others, are caused by the impacts of development, lack of local government attention to the survival of rural communities, shifting jobs and failure to get jobs and creating a businesses then make the community poorer. This study aims to describe the condition of poverty in marginalized communities by taking the case in Cipacing Village, Jatinangor District, Sumedang Regency. Cipacing village has the most disadvantaged families compared to other villages in Jatinangor Sub-district. Understanding of marginal communities in this study uses the marginal dimension according to Perlman, namely marginal social, marginal culture, marginal economy, and marginal politics. This study uses qualitative methods with descriptive analysis, data collection in research using interviews and secondary data such as the results of other studies, books, and other documentation. The number of informants involved in this study were 6 people who were poor families in Cipacing Village. The result of this study is that marginalized communities have indeed lost their rights since the development. In addition, development also has an impact on people's lives, especially in the field of environment and community welfare. The conclusions raised from this study include that the poor in Desa Cipacing are seen from the marginal dimension of society. From the social dimension, there are not many people in Cipacing Village involved in the development within their area. From the cultural dimension, the community is not ready when there is a shift in employment from the agricultural sector to the industrial sector. Then from the economic dimension, limitations in resources result in people being unable to fight capital ownership. Furthermore, from the political dimension the community also still cannot access their rights in development planning.